A New Microhardness Testing Method on Grating Films. (17th February 2020) - Ma, Haitao; Jin, Yi; Jirigalantu,
Abstract : The manufacturing process of large-area, high-precision gratings is a very complicated and time-consuming process. The hardness testing of grating films is an important step in the entire process. In order to simplify the manufacturing process of gratings, we have proposed a new method for testing microhardness based on tool edge indentation. Also, it unified tool adjustment and microhardness testing steps in the grating manufacturing process. First, a mathematical model of the relationship between tool load and indentation contour length is established. The model parameters were then modified using tool indentation experiments with different loads. When measured with a nanoindenter, the average hardness of the grating film was 447 MPa. The hardness value of the grating film obtained by our proposed method is almost the same as that measured by the nanoindenter, and the maximum deviation is about 2.2% of the average hardness value. The experimental results show that our proposed method can replace the microhardness test method of using a nanoindenter. Therefore, the disadvantages of using a nanoindenter to test the hardness of a grating film are avoided, such as the limited sample size, the sensitivity of the indenter to the roughness of the film and the depth of the indentation, and the accuracy of film testing, and the efficiency of grating ruling can be improved.